2013
DOI: 10.1038/cddis.2013.335
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin promotes oligodendrocyte precursor recruitment and remyelination after spinal cord demyelination

Abstract: Adult oligodendrocyte precursor cells (OPCs) are located adjacent to demyelinated lesion and contribute to myelin repair. The crucial step in remyelination is the migration of OPCs to the demyelinated area; however, the mechanism of OPC migration remains to be fully elucidated. Here we show that prostacyclin (prostaglandin I2, PGI2) promotes OPC migration, thereby promoting remyelination and functional recovery in mice after demyelination induced by injecting lysophosphatidylcholine (LPC) into the spinal cord.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…Spinal cord demyelination causes severe motor deficits, which recover in a time-dependent manner as a result of spontaneous remyelination (14,38). Therefore, we speculated that peripheral FGF21 is involved in improvement of motor function.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Spinal cord demyelination causes severe motor deficits, which recover in a time-dependent manner as a result of spontaneous remyelination (14,38). Therefore, we speculated that peripheral FGF21 is involved in improvement of motor function.…”
Section: Discussionmentioning
confidence: 98%
“…For example, plateletderived growth factor (PDGF) and basic fibroblast growth factor (FGF), which are expressed by astrocytes (10), are both important for OPC proliferation (12). Other studies have shown that factors secreted by vascular cells promote remyelination (13,14). Consistent with these findings, the CNS is isolated from the peripheral milieu by vascular barriers such as the blood-brain barrier (BBB) and blood-spinal cord barrier.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…OPC proliferation is enhanced by treatment with growth factors such as platelet-derived growth factor (PDGF) and basic fibroblast growth factor (FGF2) [20] . So far, the molecular mechanism of remyelination has been attributed to the factors produced by the CNS cells, such as astrocytes [21,22] , microglia [23,24] , and vasculature [25] , because the CNS is normally separated from the periphery in the presence of a vascular barrier (blood brain barrier [BBB], blood spinal cord barrier). However, several CNS regions (e.g.…”
Section: Remyelinationmentioning
confidence: 99%
“…To investigate whether the observation in vitro is consistent with in vivo remyelination, we used a lysophosphatidylcholine (LPC)-induced demyelination model mouse [35,36] , which also reveals spontaneous remyelination [25] . In this model, although we did not detect significant neuronal loss by the measurement of NeuN-positive cell number around the LPC injection site in the spinal cord, damage of the vascular barrier around the lesion site was found [37] .…”
Section: Leptin Is Involved In Spontaneous Remyelination In Vivomentioning
confidence: 99%